The The Role of Islamic Religious Counselors in Disseminating Family Education Values: A Socio-Cultural Perspective at the Office of Religious Affairs of Arungkeke District - Milda Apriliana; Farhan Aprisal (LECTURES: Journal of Islamic and Education Studies, 2026)
This study aims to examine the role of Islamic religious counselors in promoting family education values at the Office of Religious Affairs in Arungkeke Subdistrict, Jeneponto Regency, using a socio-cultural approach. In the context of the dynamics of modern Muslim families, religious counselors play a strategic role as agents of change by instilling faith-based educational values in society, particularly among prospective brides and grooms. This research employs a qualitative approach, with data collected through observation, in-depth interviews, and documentation of counseling activities carried out at the KUA. The findings indicate that religious counselors actively promote family education through premarital counseling, direct education during the marriage registration process, and the use of both print and digital media. The communication strategies employed combine persuasive and cultural approaches, taking into account the social conditions and local wisdom of the Arungkeke community. These findings highlight that the role of religious counselors is not merely administrative but also educational and transformative in fostering family resilience based on Islamic values. The study recommends strengthening counselor capacity and cross-sector collaboration to expand the reach and effectiveness of counseling at the grassroots level.